Narrativizing Trauma of the People’s War in Shrestha’s “Monologues” - Pokhrel, Badri Prasad (Interdisciplinary Journal of Management and Social Sciences, 2024)
In this study, I scrutinize and analyze Nepali jan yuddha and its impacts on common denizens living under the threat of both the rebels and the security forces narrativized in Abhinash Shrestha’s “Monologue” from the perspective of trauma studies. In the process of the research, the paper intends to show the violence, futility of war, enormous pain, fear, estrangement, unhappiness and shadow of war hanging in the mind of survivors basically those people living in the hinterlands of Nepal and expecting peace as soon as possible. Watching news on television and reading newspapers, they are seen longing for harmonious relationship in all. The specter of violence has been imprinted in all people’s mind and murder, manhandling, abusing and kidnapping in front of the family members have been common to all. Following this and using some critical insights of Caruth’s trauma theories and others’ as theoretical parameter, I have analyzed the primary text. This paper also intends to bring out the prospects of peace and solidarity among the people living under the threat from both sides, besides the enhanced conflict which has terrorized everyone. Discussing the expected findings, this article focuses on common individual’s anticipation for peace in the war-ridden societies.